Optimization of Green Synthesis of Selenium Nanoparticles and Evaluation of Their Antifungal Activity against Oral Candida albicans Infection - Mohsen Safaei; Hamid Reza Mozaffari; Hedaiat Moradpoor; Mohammad Moslem Imani; Roohollah Sharifi; Amin Golshah (Advances in Materials Science and Engineering)
Increasing resistance of microbes to available antimicrobial agents has necessitated the production of new compounds with wider activity and lower toxicity. Candida is one of the pathogenic fungal strains that are highly prevalent in oral diseases. The goal of this study was to optimize the biosynthesis of selenium nanoparticles (NPs) with the suitable antifungal activity on Candida albicans oral pathogen. For this purpose, selenium NPs were synthesized by the green method using the Halomonas elongata bacterium. To optimally synthesize NPs with the maximal antifungal properties, 9 experiments were planned applying the Taguchi method. In the planned experiments, the efficacy of 3 factors, sodium selenite concentration, glucose concentration, and incubation time at 3 various levels was studied, and the most desirable conditions with the suitable performance were determined. Then, optimizing the synthesis of the studied nanoparticles, their properties were evaluated using Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-Vis), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), electron transmission microscopy (TEM), and thermogravimetric analysis (TGA) to confirm the synthesis of nanoparticles with suitable conditions. The results demonstrated that the synthesized NPs in the experiment 9 condition showed the best performance and prevented more than 70% of fungal growth. Since selenium NPs were effective as an antifungal agent, they can be used in the structure of mouthwashes as an antimicrobial agent in the prevention and treatment of many oral diseases.